Utility of anticipatory management approach in regulating motorcycle public transport in Kisii town, Kenya - Sibwoga, Veronicah N; Angawa, Francis; Tonui, Warkach K. (Researchjournali, 2015)
The use of Motorcycles Public Transport (MPT) is partly the cause of heavy traffic congestion in Kenya’s urban centers. Sustainable urban transport implies systematic change in approaches to urban transport service provision, regulation and efficiency improvement. This study was conducted in Kisii town, Western Kenya, a medium-sized town characteristic of high Motorcycle-related Traffic Congestion (MTC). Several scenarios in Kisii town have promoted and sustained use of MPT despite it being uncomfortable, unsafe and unreliable. These include; rapid urban sprawl, increasing travel distance, high travel demand, failed urban infrastructure, laxity in law enforcement and continued population increase. The study revealed that the introduction and continued use of MPT has compounded the transport problem in Kisii town. With minimal policy interventions, the town will remain locked in traffic uncertainties and an eventual urban transport crisis too expensive to handle is pending. However, this paper presents an opportunity to solve the transport problem in the town through use of Anticipatory Management Approach (AMA). Results of this study revealed that 61.4% of the respondents agreed that AMA will control MPT. Still, 21.3% saw AMA as a good strategy to be adopted in reducing MTC while 17.3% recommended that the approach will help the study community to create sustainable urban travel modes. The benefits accruing from the use of MPT are many but the risks and danger thereof are equally great. Overall, radical policy interventions should be initiated through AMA models and residents should be educated to enable them make informed choices in the steadily changing urban transport modalities. Improvements should also be made on the town’s transport infrastructures to control MPT and create sanity in the Kisii town public transport industry.
Keywords: Motorcycle; Public; Transport; Traffic; Congestion; Anticipatory Management Approach; Kisii; Kenya